Growth Promotion of Rice (Oryza sativa L.) Seedlings Using Plant Growth-Promoting Rhizobacteria (PGPR) Isolated from Northwest Ethiopia - Zewdu Teshome Awlachew; Gebeyehu Yibeltie Mengistie (Advances in Agriculture)
Plant growth-promoting rhizobacteria (PGPR) are beneficial soil microorganisms that colonize plant roots and enhance plant growth by a wide variety of mechanisms. In this work, five Bacillus and two Cyanobacteria isolates were successfully isolated and characterized. A pot experiment was conducted to evaluate the effect of PGPR on the growth of three cultivars of rice seedlings. Pots were laid down in a complete random design and 100 ml of spore and Cyanobacteria suspension were poured on the soil surface surrounding each seedling. After 45 days, the seedlings were uprooted and shoot and root parameters were recorded. All the Bacillus and Cyanobacteria isolates showed positive effects on the growth of rice seedlings as compared to control; however, their effectiveness varies from isolate to isolate and also from cultivar to cultivar. Bacterial isolates B3 and B5 showed the highest mean value and statistically significant difference (P<0.05) in most of the root and shoot parameters of cultivars Jegna and Getachew, respectively, as compared to other bacterial isolates. Both cyanobacterial isolates showed the highest and statistically significant difference (P<0.01) in almost all the above ground and underground growth parameters compared to other bacterial isolates in all the three cultivars of rice. Similarly, C2 and C1 recorded the highest growth promotion efficacy of shoot and root length (50.07% and 78.27%) on Edget and Getachew cultivars, respectively. Hence, the present study suggests that the use of PGPR isolates such as B3, B5, C1, and C2 as inoculant biofertilizers might be beneficial for rice cultivation as they enhanced the growth of rice seedlings.